2009
DOI: 10.1111/j.1447-0756.2009.01036.x
|View full text |Cite
|
Sign up to set email alerts
|

Transvaginal cystocele correction: Midterm results with a transobturator tension‐free technique using a combined bovine pericardium/polypropylene mesh

Abstract: The use of a composite bovine pericardium/polypropylene mesh for cystocele correction is feasible and safe, yielding good results at midterm follow up.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
2

Year Published

2010
2010
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 36 publications
0
5
0
2
Order By: Relevance
“…This patient presented with vaginal irritation and dyspareunia, and the site of the exposure was at the junction between the biological graft and the synthetic arm (Riv Fix). Exposure at the biological/synthetic graft interface was also reported by Araco et al (21). The exposed part was successfully trimmed in the office with resolution of the patient's symptoms.…”
Section: Discussionmentioning
confidence: 58%
“…This patient presented with vaginal irritation and dyspareunia, and the site of the exposure was at the junction between the biological graft and the synthetic arm (Riv Fix). Exposure at the biological/synthetic graft interface was also reported by Araco et al (21). The exposed part was successfully trimmed in the office with resolution of the patient's symptoms.…”
Section: Discussionmentioning
confidence: 58%
“…No rectal injury was reported in randomized studies, versus 0.58% out of 5,877 patients in cohorts (47 NRT). Two nonrandomized studies have mentioned vaginal perforations (4.35% of 99 patients) [33,34]. Randomized studies showed no difference with or without mesh reinforcement regarding to these complications, and recently Altman confirmed this result [23].…”
Section: Visceral Injurymentioning
confidence: 97%
“…Paraiso was the only one to report a pelvic abscess after surgery [5]. In 11 non-randomized studies (623 patients), nine of which using NAS meshes, no post-surgical infection was detected [33,[36][37][38][39][40][41][42][43][44][45]. Six studies with NAS meshes reported post-surgical hyperthermia, meaning 3.15% out of 755 cases [46][47][48][49][50][51].…”
Section: Infectionmentioning
confidence: 99%
“…Les fréquences des plaies vésicales, urétrales et urétérales sont de 1,94, 1,6 et 1,55 % dans les études non randomisées, et [28,29]. Les études randomisées n'ont pas retrouvé de différence entre les techniques avec ou sans renfort pour ces complications.…”
Section: Plaies D'organesunclassified
“…Seul Paraiso rapporte la survenue d'un abcès pelvien dans les suites opératoires [6]. Dans 11 études non randomisées (soit 623) patientes), dont neuf portant sur des prothèses NRS, aucune complication infectieuse n'a été notée en période postopératoire [28,[31][32][33][34][35][36][37][38][39][40]. Six études portant sur des prothèses NRS rapportent une hyperthermie dans 3,15 % des cas en moyenne sur 755 patientes traitées [41][42][43][44][45][46].…”
Section: Infectionunclassified